(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
Infiltration experiment involve the use of large volumes of water with heavy infiltrometer. This study evaluated Kostiakov and Phillip infiltration models on the coastal plain soils of Owerri, Imo State. Four land use types; Plantain Plantation (PP), Forestry Botanical Garden (FBG), Fallow Land (FL) and Vegetable Farm (VF) were selected for the study, and two infiltration tests were carried out in situ using a double ring infiltrometer method. Kostiakov and Phillip infiltration equations were fitted based on data generated from field measurements. Basic infiltration rates for the four land uses were also determined, and they were in this order: PP > FL > FBG > VF. Plantain Plantation had the highest basic infiltration rate with a mean value of 3.95 cm/min, followed by Fallow Land (3.93 cm/min) and Forestry Botanical Garden (2.38 cm/min), while Vegetable Farm (1.40 cm/min) had the lowest basic infiltration rate. Kostiakov model generated these equations: I = 0.06t1.3,I = 0.30t1.2, I = 0.21t1.3 and I = 0.05t1.3 for PP, VF, FBG and FL while Philip model gave these equations: I = -0.90t1/2 + 7.56t, I = -0.95t1/2 + 7.56t, I = -2.76t1/2 + 9.84t, I = -1.96t1/2 + 7.05t for FL, PP,FBG and VF respectively. Philip model recorded high negative sorptive values. Root Mean Square Error (RMSE) and coefficient of determination (R2) were computed for each model to determine the best fit. The Kostiakov model gave higher R2 values and the least RMSE values; therefore, it is selected as the best fit model for the soils of the study area.